2009
DOI: 10.1177/0310057x0903700504
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia and Respiratory Events in Patients with Symptoms of Obstructive Sleep Apnoea

Abstract: Symptoms of obstructive sleep apnoea are common in patients presenting for surgery and are associated with increased morbidity. Analgesia contributes significantly to postoperative respiratory depression and obstruction, so we compared standard morphine patient-controlled analgesia with an opioid-sparing protocol (tramadol patient-controlled analgesia, parecoxib and rescue-only morphine) in these patients. Sixty-two patients presenting for elective surgery with body mass index ≥28 and signs or symptoms suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…[51][52][53] The study by Ramachandran and colleagues identified critical respiratory events during parenteral analgesic therapy for acute postoperative pain. 55 They concluded that tramadol may be a better analgesic drug for postoperative pain control in OSA patients. 54 Blake and colleagues investigated the use of postoperative morphine patient-controlled analgesia (PCA) versus an opioid-sparing protocol using tramadol PCA, parecoxib, and rescueonly morphine.…”
Section: Strategies For Pain Managements In Obese Osa Patientmentioning
confidence: 99%
“…[51][52][53] The study by Ramachandran and colleagues identified critical respiratory events during parenteral analgesic therapy for acute postoperative pain. 55 They concluded that tramadol may be a better analgesic drug for postoperative pain control in OSA patients. 54 Blake and colleagues investigated the use of postoperative morphine patient-controlled analgesia (PCA) versus an opioid-sparing protocol using tramadol PCA, parecoxib, and rescueonly morphine.…”
Section: Strategies For Pain Managements In Obese Osa Patientmentioning
confidence: 99%
“…13,32 However, researchers remain unsure and conflicted about a host of subjects relating to the pathogenesis of OSA, risk factors, perioperative management of sleep disorders and associated comorbidities. 12,17,[33][34][35][36] Perhaps, these conflicts may best be explained by Chung et al, 37 who note that most adverse perioperative complications are attributable to perioperative opioid use. The challenges of differentiating most adverse OSA events are complicated by the relationship of this breathing disorder with many related comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with findings by other researchers studying perioperative risks of OSA patients. 5,13,32,34,[38][39][40][41] The ''surgery type'' variable was influenced by the categories of surgeries found in the sample. For instance, all patients who have spine surgery in our institution are admitted to the IMU per the surgeons' protocols.…”
Section: Discussionmentioning
confidence: 99%
“…When combined with morphine, tramadol is opioid-sparing, but the effect is infra-additive [26]. Since tramadol is less likely to lead to respiratory depression and reduced gastrointestinal motility compared with pure opioid agonists at equianalgesic doses, it may be a useful choice in some patients such as those with respiratory compromise or obstructive sleep apnea, or those who have had gastrointestinal surgery [1,23,27,28]. Its effectiveness in the treatment of acute neuropathic pain may also make it a worthwhile agent in some patients [29,30].…”
Section: Discussionmentioning
confidence: 99%